E-229 Treatment of ruptured intracranial aneurysms using the novel generation of flow-diverters with surface modification: a systematic review and meta-analysis. (23rd July 2022) - Monteiro, A; Khan, A; Donnelly, B; Kuo, CC; Burke, S; Waqas, M; Housley, S; Cappuzzo, J; Levy, E; Siddiqui, A
Abstract : Background: Surface modification of flow-diverters (FD)' metallic struts has been explored as an alternative to reduce the thrombotic risk of these devices, without necessarily using potent antiplatelet therapy. Such feature, if efficient, could pose a promising alternative to the treatment of ruptured aneurysms that are not amenable to other modalities. We performed a systematic review of literature and meta-analysis of studies reporting the use of surface modified FDs to treat ruptured intracranial aneurysms to evaluate the characteristics of aneurysms treated with these devices, their periprocedural safety in the setting of SAH and outcomes. Methods: We performed a comprehensive systematic search of PubMed, MEDLINE, and Embase databases following the Preferred Reporting Items for Systematic reviews and Meta-analyses (PRISMA) guidelines. We included articles reporting the use of surface modified flow-diverters in the treatment of ruptured aneurysms. Demographics, severity of subarachnoid hemorrhage (SAH), aneurysm characteristics, devices used, complications, angiographic outcomes, and mortality were extracted. Results: Six studies comprising 59 patients with 64 aneurysms were included. Mean age of patients was 56.6 (SD ± 6.3 years) and 60.6% (95% CI 46.7%-72.9%) were women. Anterior circulation location was 60.4% (95% CI 45.5%-73.5%) of aneurysms. Aneurysms were saccular in 41.8% (95% CI 29.3%-55.4%), fusiform in 16.7% (95% CI 8.3%-30.8%), dissecting in 29.9% (95% CI 12.8%-55.4%), blood-blister in 24.4% (95% CI 15.2%-36.7%) and mycotic in 5.7% (95% CI 2%-15.1%). Poor SAH grade was reported in 46.9% (95% CI 33.3%-60.9%). Adjunctive coiling was used in 33.2% (95% CI 12.4%-63.6%). Periprocedural thromboembolic and hemorrhagic complications occurred in 20% (95% CI 7.1%-45.1%) and 8.8 (95% CI 3.7%-19.5%), respectively. Complete occlusion was achieved in 76.4% (95% CI 58.1%-88.3%), no retreatments during follow-up were reported. Overall mortality rate was 15.1% (95% CI 7.7%-27.6%). There were no differences between single and dual antiplatelet regimens with regards to periprocedural ischemic (P=0.09) and hemorrhagic (P=0.834) complications, and mortality (P=0.312). Conclusion: Surface modified FDs for the treatment of ruptured aneurysms had high rates of ischemic complications and acceptable rate of hemorrhagic complications. A relevant proportion of aneurysms were either dissecting, fusiform or blood-blister like. Rates of complete occlusion were high and retreatment was low. There were no statistical differences between SAPT and DAPT regarding periprocedural complications and mortality. Disclosures: A. Monteiro: None. A. Khan: None. B. Donnelly: None. C. C: None. S. Burke: None. M. Waqas: None. S. Housley: None. J. Cappuzzo: None. E. Levy: 2; C; Claret Medical, GLG Consulting, Guidepoint Global, Imperial Care, Medtronic, Rebound, StimMed, Misionix, Mosiac, Clarion, IRRAS. 4; C; NeXtGen Biologics, RAPID Medical, Claret Medical, Cognition Medical, Imperative Care, Rebound Therapeutics, StimMed, Three Rivers Medical. A. Siddiqui: 2; C; Amnis Therapeutics, Apellis Pharmaceuticals, Inc., Boston Scientific, Canon Medical Systems USA, Inc., Cardinal Health 200, LLC, Cerebrotech Medical Systems, Inc., Cerenovus, Cerevatech Medical, Inc., . 4; C; Adona Medical, Inc., Amnis Therapeutics, Bend IT Technologies, Ltd., BlinkTBI, Inc, Buffalo Technology Partners, Inc., Cardinal Consultants, LLC, Cerebrotech Medical Systems, Inc, Cerevatech Medical.